Laparoscopic Gastrectomy and Transvaginal Specimen Extraction in a Morbidly Obese Patient with Gastric Cancer - Sumer, Fatih (J Gastric Cancer, 2016)
Laparoscopic gastrectomy for cancer has some significant postoperative benefits over open surgery with similar oncologic outcomes. This procedure is more popular in the Far East countries where obesity is not a serious public health problem. In the Western countries, laparoscopic gastrectomy for cancer is not a common procedure, yet obesity is more common. Herein, we aimed to demonstrate the feasibility of laparoscopic gastrectomy for advanced gastric cancer in a morbidly obese patient. Additionally, we used natural orifice specimen extraction as an option to decrease wound-related complications, which are more prevalent in morbidly obese patients. In this case, we performed a fully laparoscopic subtotal gastrectomy with lymph node dissection and Roux-en-Y gastrojejunostomy with the specimen extracted through the vagina. To the best of our knowledge, this was the first report of a natural orifice surgery in a morbidly obese patient with gastric cancer.